Implementation of Sharia Economic Dispute Mediation at the Garut Religious Court in Case Number 2/Pdt.GS/2022/PA.Grt - Yulianti, Yeni; Dedah Jubaedah; Rusmani; Agi Attaubah; Jaenuddin; Muhammad Arzaki (ASAS, 2026)
The increase in sharia-based economic activity has resulted in the emergence of various potential disputes between parties, particularly between sharia financial institutions and their customers. To ensure fair, expeditious, and cost-effective dispute resolution, the religious justice system mandates mediation as part of the legal process in the Religious Courts. The issues examined in this research are how mediation is implemented in resolving sharia economic disputes and the factors influencing its success. This research aims to analyze the role and effectiveness of mediation in sharia economic disputes and identify obstacles encountered in practice. The research method used is empirical juridical with a statutory regulatory approach and a conceptual approach, supported by a literature review of primary and secondary legal materials. The results indicate that mediation is normatively regulated comprehensively and holds a significant role in resolving sharia economic disputes. However, its implementation has not been optimal due to the low level of good faith of the parties, limited understanding of sharia contracts, and the suboptimal role of mediators. This study concludes that optimizing mediation requires improving the quality of mediators and the legal awareness of the parties so that the goal of resolving disputes peacefully and fairly can be achieved.